2017
DOI: 10.1002/ijc.30756
|View full text |Cite
|
Sign up to set email alerts
|

Long-term risk of colorectal cancer after negative colonoscopy in a Danish gFOBT screening cohort

Abstract: Faecal occult blood test (FOBT) screening for colorectal cancer (CRC) is implemented in several countries. Approximately half of all screen positive persons have negative colonoscopy, but consensus is lacking on how these persons should be followed up. Health authorities in Denmark and The Netherlands recommend suspending screening for 8-10 years, while patients in UK are invited to screening after 2 years. In this cohort-study, we followed 166,277 individuals invited to FOBT-screening in 2005-2006 and a refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
7
1
1
Order By: Relevance
“…Danimarka ve Hollanda'da 8-10 yıl arayla tarama yapmak önerilse de İngiltere'de 2 yılda bir tarama yapılması önerilmiştir. Aynı çalışmada GGK pozitif olan 26.123 kişinin alındığı kolonoskopik taramadaki bireylerin yaklaşık %5'inde kolorektal kanser, %15'inde adenom tespit edilmiş (14). Paimela ve arkadaşlarının yaptıkları çalışmada GGK pozitif tespit edilen hastalar arasında invaziv kolorektal kanser tespit oranı %8,2, adenom ve kolorektal mukozal invazyon gösteren kanser oranı ise %39,7 olarak tespit edilmişti (15).…”
Section: Discussionunclassified
“…Danimarka ve Hollanda'da 8-10 yıl arayla tarama yapmak önerilse de İngiltere'de 2 yılda bir tarama yapılması önerilmiştir. Aynı çalışmada GGK pozitif olan 26.123 kişinin alındığı kolonoskopik taramadaki bireylerin yaklaşık %5'inde kolorektal kanser, %15'inde adenom tespit edilmiş (14). Paimela ve arkadaşlarının yaptıkları çalışmada GGK pozitif tespit edilen hastalar arasında invaziv kolorektal kanser tespit oranı %8,2, adenom ve kolorektal mukozal invazyon gösteren kanser oranı ise %39,7 olarak tespit edilmişti (15).…”
Section: Discussionunclassified
“…[31] Tumor detection rates are lower in patients with abdominal pain than in those with iron deficiency anemia and rectal bleeding. [32][33][34] In the present study, rectal bleeding and constipation were the leading indications for colonoscopy, with the two indications accounting for the two-thirds of the total. Although not to a statistically significant degree, GIS bleeding and anemia were the most common indications among those identified with cancer.…”
Section: Discussionmentioning
confidence: 71%
“…The incidence of CRC after a negative colonoscopy in the context of population organized FOBT-based screening programs has only been reported in two studies that used guaiac-FOBT. A Danish study reported 14 CRCs out of 771 positive guaiac-FOBT followed by a negative colonoscopy (1.8 %) after 8 years of follow-up 11 . In that study, the individuals with positive FOBT and subsequent negative colonoscopy had the same long-term CRC risk as individuals with positive FOBT and adenomas and as the unscreened reference population 11 .…”
Section: Discussionmentioning
confidence: 99%
“…A Danish study reported 14 CRCs out of 771 positive guaiac-FOBT followed by a negative colonoscopy (1.8 %) after 8 years of follow-up 11 . In that study, the individuals with positive FOBT and subsequent negative colonoscopy had the same long-term CRC risk as individuals with positive FOBT and adenomas and as the unscreened reference population 11 . Based on these results, the authors suggested that a 10-year interval of screening may not be safe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation